Temperature and precipitation projections over Bangladesh and the upstream Ganges, Brahmaputra and Meghna systems. Issue 6 (21st April 2015) - Caesar, J.; Janes, T.; Lindsay, A.; Bhaskaran, B.
Abstract : High resolution climate change simulations for south Asia are evaluated and show the changes projected during the 21 st century. Abstract : South Asia is a region of complex atmospheric dynamics and therefore changes resulting from increasing greenhouse gas concentrations, combined with existing vulnerability to extreme weather events such as flooding, could put the region at particular risk from climate change. However, current climate projections for the region show a range of uncertainty, particularly in terms of changes in the variability and extremes of precipitation. Focusing on Bangladesh and the region encompassing parts of the Ganges, Brahmaputra and Meghna river basins, we aim to explore and quantify climate model uncertainty in climate change projections for the 21 st century. We use results from a 17-member perturbed physics ensemble of projections from a global climate model which have been used to drive a higher resolution (25 km) regional climate model over the south Asia region from 1971 to 2099. The range of temperature and precipitation responses across the ensemble are assessed including representation of the annual cycle, trends, and changes in precipitation extremes. The 17 ensemble members consistently simulate increasing annual mean temperatures by 2100 compared with present day, ranging between 2.6 °C and 4.8 °C. Additionally, all ensemble members indicate increasing annual precipitation by 2100 of between around 8% and 28%, though with interdecadal variability which results in one ensemble member showing a slight decrease in precipitation in the mid-century period. The frequency of light precipitation events is projected to decrease in the future, but with an increase in the frequency of heavy events. Three members of the climate model ensemble, representing a range of projected climate outcomes, have been selected for use in further impacts modelling for the region.